Generate a plan and describe the steps needed to solve the equation 34=-(m+3)

HEEEEEEEEEELLLLLLLLLLPPPPPPPPPPPP MMMMMMMMMMMMEEEEEEEEEEEEEEE

Respuesta :

Answer:

m=-37

Step-by-step explanation:

First, you would distribute the negative sign into the equation, which will give you 34= -m-3. Then you would flip the equation so that it is -m-3=34. Second, you would add 3 to both sides to get -m=37. Third, you would divide each sides of the equation by -1, which will get m=-37. Hope this helps.

Sample Response: The negative sign outside the parentheses represents –1. Distribute the –1 to everything inside the parenthesis. Use the addition property of equality first to add 3 to both sides. Then use the division property of equality to divide both sides by -1.